Influence of Remuneration and Job Security on Organizational Performance of Co-operative Bank Branches in Kiambu County, Kenya - Colleta Wanjiru Maina; Simon Nyakwara (IJRDO - Journal of Business Management, 2020)
In a highly competitive, global environment, organizations are constantly under pressure to retain their workforce. Highly skilled, reliable and experienced employees are a valuable asset for any organization. It is evident that highly motivated employees are more likely to have high productivity. The purpose of this study was to investigate the influence of job security on organizational performance at Co-operative Banks, Kiambu County. The study specifically; investigated the influence of remuneration on organization performance at Co-operative Banks, Kiambu County; determined the influence of job security on organizational performance at Cooperative Bank, Kiambu County. The study will benefit the, academicians, policymakers and community members. The study adopted descriptive research design with a target population of 101 members. The study adopted a stratified random sampling technique and sample survey, thus, using the whole target population. The study used structured questionnaires as the main tool of data collections. The instrument was validated by the supervisors. Reliability of the instrument as determined through a pilot study. Thereafter, the Cronbach alpha coefficient was 0.72 was obtained from the instrument. This indicated the instrument was reliable, quantitative data that remuneration, job security, recognition and praise and promotion and growth affect organization performance.